Analysis of the Realization of the Regional Revenue and Expenditure Budget in Increasing the Development of Coastal Areas in the Kulon Progo Regency Area - Andi Fajar Asti; Marja Sinurat (Formosa Journal of Sustainable Research, 2023)
Kulon Progo Regency has the potential to improve coastal areas, but because of the impact of evictions on airport construction it has an impact on the lives of pond farmers. The shift in land use causes a shift in people's lives and economic activities. This requires government support in implementing decentralization to improve the quality of coastal area communities and development that can benefit the community and increase regional income. Research Method The type of research used in the research is a descriptive method with a qualitative approach. The focus of this research is: regional financial planning and implementation, responsibility for responsibility and financial reports, asset management in planning, implementation and supervision of regional assets. Problems become obstacles in financial management and supporting factors. The government provides input to encourage people to take advantage of business opportunities in coastal areas. Government support is very necessary to support social and economic disparities. It is hoped that APBD assistance will be able to help, carry out programs that have been determined by the Forestry and Maritime Service government. The APBD distributed must remain targeted to develop sustainably so that the community can support the economy to meet their daily needs